Online TeleHealth of Mind-body Interventions Versus Face-to-Face Counseling and the Health-related Quality of Life in Women with Polycystic Ovary Syndrome: A Randomized Clinical Trial - Maryam Javanbakht; Tahmineh Farajkhoda; Akram Ghadiri Anari; Hassan Zareei Mahmoodabadi (Mashhad University of Medical Sciences, 2024)
Background & aim: Limited studies have been conducted on the effectiveness, applicability, and satisfaction of mind-body interventions as short-term methods that affect body conditions like Polycystic Ovary Syndrome (PCOS). Therefore, this study aimed to compare the efficacy of online mind-body interventions versus face-to-face counseling on the quality of life (QOL) of women with PCOS.Methods: This parallel randomized clinical trial was implemented in Yazd in 2020.  Sixty eligible women with PCOS were randomly allocated to the online group (n=30) and face-to-face counseling (n=30) groups. Eight 120-minute sessions of mind-body interventions were held for both groups, either as online or face-to face. Data was collected using the PCOS Health-Related Quality of Life (HRQOL) questionnaire (at baseline, week 8 and 12), counseling satisfaction scale (at week 8 and 12), and FBS (at baseline and week 8) in both groups. Data were analyzed by SPSS (version22) using T-test, and repeated measures ANOVA.Results:  HRQOL was 94.87±11.75 in online and 90.50±9.76 in face-to-face group at baseline, which increased significantly to 108.53±4.5 in the online and face-to-face groups at week 12, with a greater increase in the online group (P<0.001). Satisfaction with counseling increased at week 12 compared to week 8 in both groups, which was not significantly different (P=0.31). FBS decreased at week 8 compared to baseline in both groups without a significant difference (P=0.26).Conclusion: The greater effectiveness of online mind-body interventions on HRQOL in women with PCOS highlights their potential value as telehealth interventions.